Crustal structure beneath SE Tibet from joint analysis of receiver functions and Rayleigh wave dispersion. Issue 5 (7th March 2014) - Sun, Xiaoxiao; Bao, Xuewei; Xu, Mingjie; Eaton, David W.; Song, Xiaodong; Wang, Liangshu; Ding, Zhifeng; Mi, Ning; Yu, Dayong; Li, Hua
Abstract New constraints on the pattern of crustal flow in SE Tibet are obtained from joint analysis of receiver functions and Rayleigh wave dispersion with a newly deployed seismic array. The crust in the Sichuan‐Yunnan Diamond Block has an average thickness of 45 km and gradually thins toward the Indo‐China Block to the west and the Yangtze Block to the east. High VP/VS ratios are detected to the west of the Xiaojiang fault, but not in the Yangtze Block to the east. The S wave velocity profile reveals that intra‐crustal low‐velocity zones (IC‐LVZs) are strongly heterogeneous, with two LVZs in the middle and mid‐lower crust, respectively, in marked contrast to previous observations of a single LVZ. Combined with other observations, the two IC‐LVZs are interpreted as isolated channels of crustal flow at different depths beneath SE Tibet, resulting in the observed complex pattern of radial anisotropy and further elucidating patterns of flow and deformation.